2002
DOI: 10.1007/bf02345298
|View full text |Cite
|
Sign up to set email alerts
|

Modulating effect of respiration on atrioventricular conduction time assessed using PR interval variation

Abstract: Respiratory sinus arrhythmia (RSA) is the variation of heart rate (or RR interval) in phase with respiration and has been extensively studied. However, the effect of respiration on atrioventricular conduction delay (and hence PR interval length) has not yet received much attention. This work reports on measurements of respiration and associated RR and PR variability, in 11 subjects, assessed through surface electrocardiogram measurements, for both paced and spontaneous respiration in the supine position. A wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, the spectrum analysis of these oscillations was not carried out. The wave structure of AV interval oscillations were examined only in few papers [6][7][8]10]. The nature of these oscillations was not studied in details, and the corresponding data on animals are absent.…”
mentioning
confidence: 99%
“…However, the spectrum analysis of these oscillations was not carried out. The wave structure of AV interval oscillations were examined only in few papers [6][7][8]10]. The nature of these oscillations was not studied in details, and the corresponding data on animals are absent.…”
mentioning
confidence: 99%
“…In [20], we showed that the accuracy of automated PP and PR interval estimation was comparable to that of a human expert. To capture the "average" changes provoked by the supine-to-standing transition, Figure 7.2a shows the median PP and PR interval for all 20 subjects on a beat-by-beat basis in a 300-beat window centered around the standing event.…”
Section: Resultsmentioning
confidence: 68%
“…The PP (P-wave onset to following P-wave onset), PR (P-wave onset to following QRS onset), and RP (QRS onset to following P-wave onset) intervals were extracted using a wavelet-based technique [20]. In [20], we showed that the accuracy of automated PP and PR interval estimation was comparable to that of a human expert.…”
Section: Resultsmentioning
confidence: 86%
“…Similar wave oscillations of atrioventricular (AV) interval were detected [2,9,10,12], spectral analysis thereof was carried out, transmitter nature was investigated, and ratio between the wave structure of AV interval and cardiac contractions period (RR interval) was studied in cats [2]. Here we studied the effect of barbiturate narcosis, one of the most prevalent methods of anesthesia in physiological experiments, on the wave structure of AV interval and its ratio with the RR interval wave structure.…”
mentioning
confidence: 99%